2021
DOI: 10.1080/01419870.2021.1925320
|View full text |Cite
|
Sign up to set email alerts
|

Channel crossings: offshoring asylum and the afterlife of empire in the Dover Strait

Abstract: In 2020, over 8,400 people made their way from France to the UK coast using small vessels. They did so principally in order to claim asylum in the United Kingdom (UK). Much like in other border-zones, the UK state has portrayed irregular Channel crossings as an invading threat and has deployed a militarized response. While there is burgeoning scholarship focusing on informal migrant camps in the Calais area, there has been little analysis of state responses to irregular Channel crossings. This article begins t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Mass displacement of individuals across the globe stems from a well-founded fear of persecution for reasons of race, nationality, religion, social group, or political opinion (United Nations Convention, 1951), with the scale of the crisis more than doubling over the past decade due to the additional impacts of climate change (Berchin et al, 2017) and the COVID-19 pandemic (Raju & Ayeb-Karlsson, 2020). Border closures and industrial action post Brexit have also exacerbated the trauma inherent in the asylum-seeking process (Davies et al, 2021), with more than 8,400 individuals risking their lives attempting to cross the perilous English Channel by small vessel due to of a lack of safe alternative routes (Timberlake, 2021). The Home Affairs Committee (2020) confirmed that 98% of these individuals have applied for asylum, despite reports that the United Kingdom is a hostile immigration environment aiming to significantly reduce its net migration (Gentleman, 2019).…”
Section: The Need For a Comprehensive Scoping Reviewmentioning
confidence: 99%
“…Mass displacement of individuals across the globe stems from a well-founded fear of persecution for reasons of race, nationality, religion, social group, or political opinion (United Nations Convention, 1951), with the scale of the crisis more than doubling over the past decade due to the additional impacts of climate change (Berchin et al, 2017) and the COVID-19 pandemic (Raju & Ayeb-Karlsson, 2020). Border closures and industrial action post Brexit have also exacerbated the trauma inherent in the asylum-seeking process (Davies et al, 2021), with more than 8,400 individuals risking their lives attempting to cross the perilous English Channel by small vessel due to of a lack of safe alternative routes (Timberlake, 2021). The Home Affairs Committee (2020) confirmed that 98% of these individuals have applied for asylum, despite reports that the United Kingdom is a hostile immigration environment aiming to significantly reduce its net migration (Gentleman, 2019).…”
Section: The Need For a Comprehensive Scoping Reviewmentioning
confidence: 99%
“…Local border contexts of non-EU states prove useful to offshore security practices and violence as migration controls (Davies et al, 2021), as well as to conceal the consequences of "pushes" (Isakjee et al 2021). EU authorities view Northern Bosnia and Kurdish region in Turkey as unstable places and characterised by the common occurrence of human rights violations (European Commission, 2021b;Bird et al, 2020).…”
Section: Being Forced "Back"mentioning
confidence: 99%
“…Even when, on 24th November 2021, 27 asylum seekers drowned in the Channel, the UK Government doubled down on its plans to further militarise its costal borders, whilst many media outlets deployed the narrative of the "illegal migrants" seeking easy access to an overly generous welfare system. Overall, these constant attempts at re-shifting the target of anti-immigration concerns have been interpreted as the "active remaking of colonial modes of rule through the ongoing logics of authorised and unauthorised mobilities" (Davies et al, 2021(Davies et al, : 2322, keeping alive the permanent threat of racialised undeserving others: from the Empire to Europe, and back again, with chauvinism as a constant thread.…”
Section: Brexit: Reconfiguring the Migration-welfare Nexusmentioning
confidence: 99%